Territoires, images et imaginaires de quartier - Bruno Raoul (Communication)
This article examines the relation that the media come to bear on the representation of territory by targeting more specifically the "images" that the community press in a suburb of Roubaix (France) produce. The discourse analysis of these newspapers reveals how they "speak" of the neighbourhood, what territorial representation and what relationships to it are produced, and how such a designated territory "makes sense." At the core of this article is a reflection on the notion of "imagined neighbourhood." The diachronic viewpoint adopted leads the author to conclude that a socio-political conception lies behind the spatial representation of the neighbourhood and to put forward the hypothesis that local newspapers contribute to confine the neighbourhood within its own spatial scene.